Toronto’s failed smart city: intellectual property, data, and bad governance - Tusikov, Natasha (Ineffective Policies, 2025)
Public debates over smart cities typically focus on questions of surveillance, privacy, and possible socio-economic benefits from data-driven technologies. This chapter argues that public officials must have a critical understanding of intellectual property (IP) to effectively create and operate smart cities, complemented by a sound knowledge of data governance strategies, including how – or if – data should be commodified. When city officials lack this critical knowledge, the chapter argues, the result is ineffective policy, specifically badly designed smart cities with unevenly distributed innovation, ineffective public services, and smart-city vendors capturing the lion’s share of the revenue stream from smart-city technologies. The chapter examines Sidewalk Labs’ plans between 2017 and 2020 for a smart city project in Toronto. Drawing from critical data studies and the International Political Economy literature, the chapter examines primary documents related to the project, specifically the Google company, Sidewalk Labs’ June 2019 four-volume 1,500-page project plan.